Oral Ketamine in the Palliative Care Setting: A Review of the Literature and Case Report of a Patient With Neurofibromatosis Type 1 and Glomus Tumor-Associated Complex Regional Pain Syndrome - Soto, Eliezer (Am J Hosp Palliat Care, 2011)
Ketamine, an N-methyl-D-aspartate (NMDA) receptor antagonist, has been shown to be effective not only for its anesthetic properties but also for the analgesic and opiate-sparing effects. However, data on efficacy and safety of oral ketamine for the treatment of neuropathic or cancer pain syndromes is limited with most of the evidence based on small clinical trials and anecdotal experiences. In this review, we will analyze the clinical data on oral ketamine in the palliative care setting. After an extensive search using five major databases, a total of 19 relevant articles were included. No official clinical guidelines for the use of oral ketamine in this patient population were found. Studies on oral ketamine for cancer and neuropathic pain have shown mixed results which could be partially due to significant differences in hepatic metabolism. In addition, we will include a case report of a 38-year-old female with neurofibromatosis type 1 (NF1) with history of chronic, severe pain in her fingertips secondary to multiple glomus tumors which evolved into CRPS resistant to multiple therapies but responsive to oral ketamine. Based on our experience with oral ketamine, this drug should be administered after an intravenous trial to monitor response and side effects in patients with an adequate functional status. However, patients in the palliative care and hospice setting, especially the one at the end of their lives, may also benefit from oral ketamine even if an intravenous trial is not feasible.